2010
DOI: 10.1016/j.chom.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-like Cytoplasmic Kinases Integrate Signaling from Multiple Plant Immune Receptors and Are Targeted by a Pseudomonas syringae Effector

Abstract: Cell-surface-localized plant immune receptors, such as FLS2, detect pathogen-associated molecular patterns (PAMPs) and initiate PAMP-triggered immunity (PTI) through poorly understood signal-transduction pathways. The pathogenic Pseudomonas syringae effector AvrPphB, a cysteine protease, cleaves the Arabidopsis receptor-like cytoplasmic kinase PBS1 to trigger cytoplasmic immune receptor RPS5-specified effector-triggered immunity (ETI). Analyzing the function of AvrPphB in plants lacking RPS5, we find that AvrP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
946
3
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 706 publications
(1,002 citation statements)
references
References 52 publications
21
946
3
7
Order By: Relevance
“…Despite the role of the MAPKs 3, 4, and 6, the involvement of the upstream MAPKK and MAPKKK is less clear and a link to the upstream receptor complexes is missing. This could involve cytoplasmic kinases such as BIK1, which is phosphorylated upon flg22 elicitation and transphosphorylates FLS2 and BAK1 (Lu et al, 2010;Zhang et al, 2010), but interaction with the MAPK cascade has not been demonstrated. The MAPKs 3, 4, and 6 are prominent signaling kinases in many stress-related pathways mediating specific transcriptional changes.…”
Section: Open Questions In the Pamp Perception Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the role of the MAPKs 3, 4, and 6, the involvement of the upstream MAPKK and MAPKKK is less clear and a link to the upstream receptor complexes is missing. This could involve cytoplasmic kinases such as BIK1, which is phosphorylated upon flg22 elicitation and transphosphorylates FLS2 and BAK1 (Lu et al, 2010;Zhang et al, 2010), but interaction with the MAPK cascade has not been demonstrated. The MAPKs 3, 4, and 6 are prominent signaling kinases in many stress-related pathways mediating specific transcriptional changes.…”
Section: Open Questions In the Pamp Perception Pathwaysmentioning
confidence: 99%
“…BAK1 is a member of a small family of LRRRKs with partly redundant functions, and it is possible that PRRs are also regulated by other SERKs. Besides some evidence for protein phosphatases and the cytoplasmic kinase BIK1, which interacts with FLS2 and possibly BAK1 (Lu et al, 2010;Zhang et al, 2010), the dynamics, composition, stoichiometry of, and interactions within unstimulated and activated PRR complexes remain elusive.…”
Section: Open Questions In the Pamp Perception Pathwaysmentioning
confidence: 99%
“…Palmitoylation of N-terminal Cys residues is also predicted to allow reversible membrane association for CST and many other class VII RLCKs ( Fig. 4C; Sorek et al, 2009;Zhang et al, 2010). To visualize CST protein within Arabidopsis cells, we generated a CST-GFP fusion construct driven by the constitutive viral 35S promoter that could be transfected into mesophyll protoplasts.…”
Section: Localization Of Cst To the Plasma Membrane Is Supported By Nmentioning
confidence: 99%
“…A recent study has revealed that, like PBS1, BIK1 and several PBS1-like (PBL) RLCKs are also substrates of the bacterial AvrPphB protease effector . This discovery and other work suggests that a bacterial effector can suppress PAMP-triggered immunity in plants by cleaving RLCKs known (BIK1) or proposed (PBL1, PBL2) to positively interact with RLKs that bind PAMPs, including FLS2, CHITIN ELICITOR RECEPTOR KINASE1, and the EF-Tu RE-CEPTOR (Zipfel et al, 2006;Miya et al, 2007;Zhang et al, 2010). During effector-triggered immunity, another RLCK, RPM1-INDUCED PROTEIN KINASE (RIPK), is involved in activating the NB-LRR protein RPM1 (Liu et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation